Influence of Fly Ash on the Compressive Strength of Ultrahigh-Performance Concrete: A State-of-the-art Review Towards Sustainability - Rami A. Hawileh; Sayan Kumar Shaw; Maha Assad; Alinda Dey; Jamal A. Abdalla; Jae Hong Kim (International Journal of Concrete Structures and Materials)
Abstract Fly ash (FA) offers a sustainable alternative to cement in concrete, addressing environmental concerns and enhancing sustainability in construction practices. This substitution contributes to both resource efficiency and reduced carbon footprint. This review study investigated the effect of FA on the compressive strength of ultrahigh-performance concrete (UHPC). No negative effect associated with the increase in FA replacement percentage up to 60% by weight is observed in terms of compressive strength of UHPC without superplasticizer. However, higher replacement percentages are shown to negatively affect the compressive strength. Further investigations should focus on the compressive strength characteristics and limitations associated with elevated levels of FA replacement, i.e. 60–80%. A promising behaviour associated with higher replacement percentages is observed in few studies. Moreover, the superior compressive strengths observed up to 50% FA replacement after a curing period of 90 days underscore the need for a more extensive exploration of longer curing durations. Future studies should focus on investigating the properties of UHPC beyond 90 days, as such information is currently limited.